Evolution of sulfur speciation in bitumen through hydrous pyrolysis induced thermal maturation of Jordanian Ghareb Formation oil shale. (1st May 2018) - Birdwell, Justin E.; Lewan, Michael D.; Bake, Kyle D.; Bolin, Trudy B.; Craddock, Paul R.; Forsythe, Julia C.; Pomerantz, Andrew E.
Abstract: Previous studies on the distribution of bulk sulfur species in bitumen before and after artificial thermal maturation using various pyrolysis methods have indicated that the quantities of reactive (sulfide, sulfoxide) and thermally stable (thiophene) sulfur moieties change following consistent trends under increasing thermal stress. These trends show that sulfur distributions change during maturation in ways that are similar to those of carbon, most clearly illustrated by the increase in aromatic sulfur (thiophenic) as a function of thermal maturity. In this study, we have examined the sulfur moiety distributions of retained bitumen from a set of pre- and post-pyrolysis rock samples in an organic sulfur-rich, calcareous oil shale from the Upper Cretaceous Ghareb Formation. Samples collected from outcrop in Jordan were subjected to hydrous pyrolysis (HP). Sulfur speciation in extracted bitumens was examined using K-edge X-ray absorption near-edge structure (XANES) spectroscopy. The most substantial changes in sulfur distribution occurred at temperatures up to the point of maximum bitumen generation (∼300 °C) as determined from comparison of the total organic carbon content for samples before and after extraction. Organic sulfide in bitumen decreased with increasing temperature at relatively low thermal stress (200–300 °C) and was not detected in extracts from rocks subjected to HP at temperatures above around 300 °C. Sulfoxide content increased between 200 and 280 °C, but decreased at higher temperatures. The concentration of thiophenic sulfur increased up to 300 °C, and remained essentially stable under increasing thermal stress (mg-S/g-bitumen basis). The ratio of stable-to-reactive+stable sulfur moieties ([thiophene/(sulfide+sulfoxide+thiophene)], T/SST) followed a sigmoidal trend with HP temperature, increasing slightly up to 240 °C, followed by a substantial increase between 240 and 320 °C, and approaching a constant value (∼0.95) at temperatures above 320 °C. This sulfur moiety ratio appears to provide complementary thermal maturity information to geochemical parameters derived from other analyses of extracted source rocks.